Determinants of Internal Migration in Turkey: A Panel Data Analysis Approach - Doğan, Gizem Umut; Kabadayı, Aslıhan (Border Crossing, 2015)
Internal migration movements in Turkey have been a major concern for policy makers, city planners and academicians for decades. To anticipate and regulate these movements it is crucial to understand the factors behind these movements; namely the push and pull factors specific to regions. In this study it is aimed to discover the most effective determinants of the recent internal migration movements in Turkey. With this aim the internal migration patterns in 2008-2012 are examined by provinces in the context of push and pull factors of migration using a macro approach. A panel dataset is constructed by employing the available data covering time series of the economic, social and environmental aspects of provinces as well as the provincial migration movements. With this dataset it is attempted to find out the determinants of internal migration in Turkey by using panel data analysis methods. The economic factors such as job and high income opportunities; factors related to better living conditions such as education, health care and security are expected to play a significant role in pulling internal migration.